Do Adjustment Costs Affect the Corporate Investments in India: A Dynamic Panel Data Analysis - Mahakund, Jitendra (Indian Journal of Finance, 2009)
This Paper analyses the determinants of corporate investment of 597 companies during the period 1996-97 to 2005-06, and Generalized Method of Moments (GMM) technique has been used to examine the impact of adjustment costs and financial constraints on investment decisions of firms in the Indian corporate sector. We find strong support for the influence of financial factors or constraints on investment decisions. The corporate investments depend upon the size, and financial position of the companies. We estimate the adjustment speed of the optimal corporate investment across various types of companies on the basis of their leverage ratio, size, and retention ratio and found that for most of the companies, the adjustment speed has been more than 60 percent in the case of Indian corporate sector.